The role of Kurt Lück’s Mythos vom Deutschen in der polnischen Volksüberlieferung und Literatur in the research into “German East” in the 1930s - Wójcik, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2017)
The main focus of this article is an analysis of one of Kurt Lück’s most extensive works – Mythos vom Deutschen in der polnischen Volksüberlieferung und Literatur – published in 1938. The article attempts to answer the question of the status of Lück’s large work of research into the “German East” in the 1930s, and the question of how the work was evaluated by German and Polish historians, ethnologists, and literary critics. The book was also presented in the context of the anti-Polish attitude of the author, whose activities and publications were strongly influenced by National Socialism.